Mineralogical and geochemical characteristics of drinking water salt deposits - Soktoev, Bulat Rinchinovich; Rikhvanov, Leonid Petrovich; Matveenko, Irina Alekseevna (IOP Publishing, 2015)
The article presents the research results on the features of element and mineral composition of salt deposits (limescale) formed in household conditions in heat exchanging equipment. The major part of limescale is represented by two species of calcium carbonate - calcite and aragonite. We have shown that high concentrations of chemical elements in the limescale promote the formation of their own mineral forms (sulphates, silicates, native forms) in salt deposits. Detecting such mineral formations suggests the salt deposits of drinking water to be a long-term storage media which can be used in the course of eco-geochemical and metallogenic studies.
Keywords: минералогические характеристики; геохимические характеристики; питьевые воды; солевые отложения